Light-emitting thin-film field-effect transistors - Stallinga, Peter (2015)
A model for thin-film field-effect transistors in which the active layer is treated as purely two-dimensional is applied to ambipolar devices that have shown to be light emitting. This results in an adequate description of the electrical characteristics.